Kandungan kolesterol, High Density Lipoprotein (HDL) dan low density lipopro-tein (LDL) darah burung puyuh dengan pemberian aditif cair buah naga merah - Khabib Arrosichin; Vitus Dwi Yunianto; Fajar Wahyono (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The study aims to determine, assess and evaluate the content of cholesterol, high density lipoprotein (HDL) and Low Density Lipoprotein (LDL) blood quail which were treated with liquid additive red dragon fruit. Materials used in the study were 200 female quails aged 14 days with an average weight of 13.61 ± 0.49 g. Ration composed by metabolizable energy content of ± 3000 kcal/kg and ± 20% of crude protein. The study consisted of 4 treatments and 5 replications. The treatments were (T0: without addition of liquid red dragon fruit (control); T1: addition of 5 ml liquid red dragon fruit twice a day; T2: addition of 5 ml liquid red dragon fruit once a day and T3: addition of 5 ml liquid red dragon fruit once in every two days). Blood sampling was performed in EDTA tube at the end of the study. Analysis of samples was carried out in health laboratory Semarang. The results were analyzed using analysis of variance (ANOVA). The study showed that the addition of liquid red dragon fruit additive had no significant effect (P> 0.05) on cholesterol, HDL and LDL of quil’s blood. Keywords: Quail, cholesterol; HDL, LDL, and red dragon fruit